A checklist of the millipedes (Diplopoda) of Laos - Likhitrakarn, Natdanai; Golovatch, Sergei I.; Panha, Somsak (Zootaxa, 2014)
At the present, the millipede fauna of Laos comprises only 34 species from 20 genera, 13 families and 7 orders. These counts certainly represent but a minor fraction of the country’s real diversity of Diplopoda even at the ordinal level, let alone at lower ones. Based on the available information from the adjacent parts of China, Thailand, Myanmar, Vietnam and/or Cambodia, the orders Polyxenida, Sphaerotheriida, Chordeumatida, Julida and Polyzoniida must occur in Laos, may be also Glomeridesmida, Siphonocryptida and Stemmiulida, but none has been recorded there yet. Moreover, even some ubiquitous “tramp” species, such as Glyphiulus granulatus (Gervais, 1847), Trigoniulus corallinus (Gervais, 1847), Desmoxytes planata (Pocock, 1895) or Oxidus gracilis (C. L. Koch, 1847), have hitherto not been found in Laos. This shows that a lot more collecting efforts, which have heretofore been rather strongly biased to caves, are required to amass a representative material of Diplopoda of Laos and make it available for study.